Hak-hak Perempuan dalam Pandangan Islam - Haerullah, Haerullah; Mujahid, Kasori (Lembaga Yasin AlSys, 2024)
A long time ago, some cultures had social hierarchies that placed women on a lower level than men. They often have limited access to education and are rarely involved in political affairs or important decisions in society. However, with the advent of Islam, great attention was paid to women and they were given high dignity. In Islam, women are considered partners for men in carrying out the responsibilities of life. Allah affirms that women are men's companions in carrying out the role of caliph in this world. The purpose of this paper is to explore the rights and status of women in modern society, as well as to counter traditional ideas that are still influential from past cultures, both in the social, cultural, and political spheres. Thus, this study includes an analysis of the position and rights of women according to an Islamic perspective.